Numerical study on the microcrack propagation mechanism in pre-fabricated red sandstone with double fissures under different confining pressures - Zhao, Weisheng; Liu, Xiangru; He, Wei (Frontiers in Earth Science, 2025)
Fractured rock masses are widely distributed in geological and engineering fields, and their microcrack evolution and propagation mechanisms directly affect structural stability. To investigate these mechanisms in defective rocks, this study establishes a numerical model of pre-fabricated parallel double-fissure red sandstone using particle flow code (PFC2D). The fissures, inclined at a 45° angle to the direction of the applied stress, simulate microcrack initiation, propagation, and coalescence under different confining pressures. The results indicate that an increase in confining pressure causes the failure mode of the specimen to shift from tensile splitting failure to shear failure, a mechanism primarily controlled by the coalescence of tensile microcracks. At the fissure tips, reverse wing cracks initially form and further develop into reverse shear planes under high confining pressure conditions. The microcrack shear-tensile ratio (MSTR) is positively correlated with confining pressure and peak strength. The number of tensile microcracks at the peak stress increases stepwise with increasing confining pressure, with critical confining pressures identified at 0 MPa, 10 MPa, and 20 MPa. In contrast to tensile microcracks, shear microcracks are more sensitive to the confining pressure, indicating that higher confining pressures more easily induce shear microcrack initiation, although their quantity remains significantly lower than that of tensile microcracks. Numerical analysis further reveals that the stress concentration at the fissure tips, compression-induced tensile effects, and the deflection of contact force directions are the primary driving factors for the initiation, propagation, and coalescence of microcracks. This study provides a theoretical basis for predicting the fracture behavior of defective rock masses and offers valuable insights for engineering applications such as tunneling, slope stability, and underground excavation, where confining pressure critically influences rock failure mechanisms.